DETERMINAN KEPUTUSAN PEMBELIAN MAKANAN HALAL - Ali Hardana, Ali Hardana; Nasution, Jafar; Anugrah Nasution, Ananda (Jurnal Edueco, 2023)
Abstract: The halal food industry is growing rapidly in Indonesia. One of them is boiled snail street food in Padangsidimpuan City. Research was conducted on 99 consumers of boiled snail street food. This research uses quantitative research with instrument testing through validity and reliability tests. Then multiple linear regression analysis is used to determine the effect of the independent variable on the dependent variable. The results show that the variables price, halal awareness and level of religiosity have a positive and significant effect on the decision to purchase halal food at the Adangsidimpuan boiled snail street food. Other findings in this research show that the halal label variable has no influence on the decision to purchase halal food at Padangsidimpuan boiled snail street food.